Diplomado en simulación gerencial y responsabilidad social empresarial (2022)
As a work team, we assumed the role of executives of the Delta company, in the economic sector of technology, with the objective of managing the company for 4 periods. The companies started with the same resources, but with the difference that they were geographically located in other places. In this context, and using the CompanyGame simulator, which functions as a "Business Simulator Platform", the company in question was to be managed by means of period-based decisions; the platform allows adjusting production variables, prices, markets and training, as the most important ones. In the development of the activity and after the decisions taken, this company achieved results of 3,475 in company value, derived from variables such as economic, with a score of 1,307, and a market share of 640 points, among other indicators, which placed the company among the three (3) best of the world one (1) and the five (5) best of the two, as far as this value is concerned.